Crisis and continuity at the Abbasid court : formal and informal politics in the caliphate of al-Muqtadir (295-320/908-32) - Berkel, Maaike van. (Islamic History and Civilization, 2013)
The reign of al-Muqtadir (295-320/908-32) is a crucial and controversial epoch in the history of the Abbasid empire. Al-Muqtadir's regime has traditionally been depicted as one of decline, when the political power of the caliphate and the lustre of its capital began to crumble. This book not only offers a substantial investigation of the idea and reality of decline, but also provides new interpretations of the inner workings of the court and the empire. The authors, four specialists of Abbasid history, explore the formal and informal power relationships that shaped politics at the court, involving bureaucrats, military, harem, courtiers and of course al-Muqtadir himself. A study of the topography of Baghdad completes this vivid picture of the court and its capital.